Praktik Komunikasi Persuasif Host Live TikTok dalam Kompetisi Perang Koin - Ulul Azmi; Rafinita Aditia (Jurnal Ilmiah Global Education, 2026)
This study aims to analyze the persuasive communication practices used by TikTok Live hosts in the Perang Koin competition. This study uses a qualitative approach with a descriptive method to describe the application of persuasion strategies used directly during the broadcast. The research subjects consisted of four Indonesian hosts selected based on the criteria of actively participating in the competition at least three times a week, having a high intensity of verbal communication, and receiving active responses from the audience. The four hosts represented different audience size categories, namely @sweetlycandy2505 (1–100 viewers), @emak.dan. abah5 (100–1000 viewers), @fikinaki (1000–10,000 viewers), and @rianarifinnn09 (more than 10,000 viewers). The results of the study show that hosts apply Cialdini's principles of persuasion, such as liking, reciprocity, unity, scarcity, social proof, and authority, dynamically according to the stages of the competition and audience responses. Hosts with low viewership tend to use emotional and personal approaches to build rapport, while hosts with high viewership emphasize an authoritative and theatrical communication style that emphasizes urgency and group solidarity. Persuasive communication in Coin War is performative, emotional, and adaptive, where the host's ability to adjust their communication style and manage emotions plays an important role in encouraging audience participation and digital gift-giving behavior.